Al-Nakirah wa al-Ma'rifah fi Surati al-Naba'/النكرة والمعرفة في سورة النبأ - Yusuf, Eka Sandri; Pakaya, Nurul 'Aini; Saleh, Sriwahyuningsih R.; P. Doni, Chaterina (Universitas Muhammadiyah Gorontalo, 2024)
Surah An-Naba' in the Holy Qur'an is one of the chapters rich in message and meaning. This surah employs both nakirah (indefinite) and ma'rifah (definite) nouns, which play a crucial role in conveying the message and enriching the structure of the Arabic language. To date, studies specifically addressing the types of nakirah and ma'rifah nouns and their grammatical analysis in Surah An-Naba' are limited. Therefore, this research aims to provide an understanding of the